2016
DOI: 10.3748/wjg.v22.i36.8161
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hepatitis B virus infection on hepatic metabolic signaling pathway

Abstract: A growing body of epidemiologic research has demonstrated that metabolic derangement exists in patients with hepatitis B virus (HBV) infection, indicating that there are clinical associations between HBV infection and host metabolism. In order to understand the complex interplay between HBV and hepatic metabolism in greater depth, we systematically reviewed these alterations in different metabolic signaling pathways due to HBV infection. HBV infection interfered with most aspects of hepatic metabolic responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 59 publications
3
54
2
Order By: Relevance
“…In the SACC‐PHH platform, most of the changes in gene expression relative to mock occurred at 8 dpi. However, only the HBV mono‐infected samples at 8 dpi exhibited coordinated changes of genes involved with pathways such as oxidative phosphorylation and ECM‐receptor interaction, confirming other studies that have suggested how HBV hijacks the host machinery to promote viral production and persistence . The lack of enrichment for pathways in the co‐infected versus mock samples was not surprising, given the lower level of differential gene expression.…”
Section: Discussionsupporting
confidence: 81%
“…In the SACC‐PHH platform, most of the changes in gene expression relative to mock occurred at 8 dpi. However, only the HBV mono‐infected samples at 8 dpi exhibited coordinated changes of genes involved with pathways such as oxidative phosphorylation and ECM‐receptor interaction, confirming other studies that have suggested how HBV hijacks the host machinery to promote viral production and persistence . The lack of enrichment for pathways in the co‐infected versus mock samples was not surprising, given the lower level of differential gene expression.…”
Section: Discussionsupporting
confidence: 81%
“…Chronic hepatitis B virus (HBV) infection is a main cause of chronic hepatitis, liver cirrhosis, and hepatocellular carcinoma worldwide and a major risk factor for liver‐related morbidity and mortality, especially in Asia and Africa . In addition to HBV‐associated liver disease, there is a growing body of research demonstrating the presence of metabolic derangements, especially lipid profiles, in patients with HBV infection, suggesting that there is a clinical association between HBV infection and host metabolism . Indeed, HBV is considered a “metabolovirus” because the gene expression of HBV and key metabolic genes in hepatocytes are similarly regulated .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, HBV is considered a “metabolovirus” because the gene expression of HBV and key metabolic genes in hepatocytes are similarly regulated . The underlying mechanisms of HBV‐induced disease are not fully understood yet, and there is no definitive cure available for chronic HBV infection . Thus, a clearer understanding of the metabolic pathways involved in the pathogenesis of HBV may provide new insights into potential novel targets for HBV treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolites produced from the mitochondrial tricarboxylic acid cycle, including citrate, succinate, fumarate, and acetyl‐CoA, are important regulators of signaling transduction when released from the mitochondria . Citrate synthase and succinate dehydrogenase are up‐regulated in HBV‐infected cells, leading to elevation of the corresponding metabolites such as fumarate and succinate . Succinate has been recognized as an emerging signal transducer to activate inflammatory pathways .…”
Section: The Impact Of Mitochondrial Metabolitesmentioning
confidence: 99%